2004
DOI: 10.1074/jbc.m312245200
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatitis C Virus NS5A Protein Activates a Phosphoinositide 3-Kinase-dependent Survival Signaling Cascade

Abstract: Hepatitis C virus (HCV) establishes a persistent infection, with up to 80% of infected individuals proceeding to chronic hepatitis, which in many cases may result in liver cirrhosis and hepatocellular carcinoma (HCC); indeed HCV infection is increasingly associated with the development of HCC. The long time period (up to 30 years) between primary infection and the onset of HCC implies that HCV is not directly oncogenic but in some way predisposes patients to develop tumors, though the mechanism for this is unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
184
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(200 citation statements)
references
References 36 publications
11
184
0
3
Order By: Relevance
“…We have previously shown that NS5A bound to and activated PI3K, an event which led to the downstream phosphorylation and activation of Akt (Street et al, 2004). Furthermore, NS5A induced the stabilization of b-catenin and an increase in b-catenin-dependent transcriptional activity in a manner that was PI3K dependent (Street et al, 2005).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously shown that NS5A bound to and activated PI3K, an event which led to the downstream phosphorylation and activation of Akt (Street et al, 2004). Furthermore, NS5A induced the stabilization of b-catenin and an increase in b-catenin-dependent transcriptional activity in a manner that was PI3K dependent (Street et al, 2005).…”
Section: Resultsmentioning
confidence: 97%
“…We have demonstrated previously that NS5A interacts with the p85 regulatory subunit of PI3K (Street et al, 2004). This interaction was further shown to require residues 270-300 of NS5A.…”
Section: Ns5a Interacts With Both B-catenin and The P85 Subunit Of Pi3kmentioning
confidence: 99%
See 1 more Smart Citation
“…142 This results in activation of downstream Akt, which in turn phosphorylates and inactivates Bad, a pro-apoptotic Bcl-2 homologue, thereby inhibiting apoptosis. 142,143 As shown in Fig. 1, another downstream target of Akt is GSK-3␤.…”
Section: Hepatitis C Nonstructural Protein 5amentioning
confidence: 99%
“…6,7 Among these downstream targets, the Ras-and phosphatidylinositol 3-kinase (PI3K)-dependent pathways are required to trigger cell proliferation, motility and survival. 8,9 Tetraspanins, or TM4SF proteins, compose a large group of cell surface transmembrane proteins, some of which can form complexes with integrins. Several tetraspanins appear to be particularly relevant to tumor cell metastasis.…”
mentioning
confidence: 99%